Intraspinal Grafting of Serotonergic Neurons Modifies Expression of Genes Important for Functional Recovery in Paraplegic Rats - Krzysztof Miazga; Hanna Fabczak; Ewa Joachimiak; Małgorzata Zawadzka; Łucja Krzemień-Ojak; Marek Bekisz; Anna Bejrowska; Larry M. Jordan; Urszula Sławińska (Neural Plasticity)
Serotonin (5-hydroxytryptamine; 5-HT) plays an important role in control of locomotion, partly through direct effects on motoneurons. Spinal cord complete transection (SCI) results in changes in 5-HT receptors on motoneurons that influence functional recovery. Activation of 5-HT2A and 5-HT7 receptors improves locomotor hindlimb movements in paraplegic rats. Here, we analyzed the mRNA of 5-HT2A and 5-HT7 receptors (encoded by Htr2a and Htr7 genes, resp.) in motoneurons innervating tibialis anterior (TA) and gastrocnemius lateralis (GM) hindlimb muscles and the tail extensor caudae medialis (ECM) muscle in intact as well as spinal rats. Moreover, the effect of intraspinal grafting of serotonergic neurons on Htr2a and Htr7 gene expression was examined to test the possibility that the graft origin 5-HT innervation in the spinal cord of paraplegic rats could reverse changes in gene expression induced by SCI. Our results indicate that SCI at the thoracic level leads to changes in Htr2a and Htr7 gene expression, whereas transplantation of embryonic serotonergic neurons modifies these changes in motoneurons innervating hindlimb muscles but not those innervating tail muscles. This suggests that the upregulation of genes critical for locomotor recovery, resulting in limb motoneuron plasticity, might account for the improved locomotion in grafted animals.